Hand grip strength: A reliable, reproducible, cost-effective tool to assess the nutritional status and outcomes of cirrhotics awaiting liver transplant. (June 2017) - Daphnee, D.K.; John, Sheila; Vaidya, Anil; Khakhar, Anand; Bhuvaneshwari, S.; Ramamurthy, Anand
Summary: Background & aim: Malnutrition (MN) in patients with cirrhosis awaiting liver transplant (LTx) has been shown to be an important determinant of outcomes. Hence there is an impetus on early diagnosis and stratification to guide goal directed nutritional intervention. The aim of this study was twofold; first, to assess the effect of MN on mortality in patients awaiting LTx and, second, to evaluate HGS as a reliable, non-invasive, and inexpensive tool that can be used in routine clinical practice for early diagnosis and stratification of severity of malnutrition in patients awaiting LTx. Methods: Adults evaluated for LTx and accepted as suitable candidates were enrolled on a waiting list at a single centre between May 2014 and February 2016 and were prospectively included. Nutritional status was assessed by Subjective Global Assessment (SGA), anthropometry, and dominant hand grip strength (HGS). Statistical analysis was performed using Pearson correlation, t-test, and Receiver Operating Characteristic (ROC curve) in SPSS version 16.0. Results: One hundred eighty patients (81% male) aged 51.6 ± 10 years, (Child's C 70.6%, B 26.1%, A 3.3%) were included and followed up till LTx or end of study. Eighty seven patients (48%) who underwent LTx were excluded from the final analysis. Of the 93 patients on the waiting list, 46 (49%) were alive and revealed a high (88%) incidence of MN as assessed by SGA. There was a significant increase in MN with increasing Model End stage Liver Disease (MELD) and Child score, and decreasing HGS (p < 0.05). As per the normative standards of Hand grip dynamometer, 99% had impaired HGS (<85%). Univariate analysis showed a significant increase in mortality on the wait list with increasing MN, increasing MELD and Child score, and decreasing HGS (p < 0.05). Binary logistic regression analysis revealed HGS as an independent factor influencing mortality with an Odds ratio of 7.8. A cut off value of 19.5 kg on HGS was found to be significant in differentiating survivors from non-survivors awaiting LTx with optimal sensitivity and specificity of 67% and 75% with area under ROC curve 0.736 (95% confidence interval, 0.63–0.85). Conclusions: HGS is a reliable, non invasive and cost-effective tool to identify MN in cirrhotic patients. Low HGS (≤19.5 kg) was a strong predictor of mortality in wait-listed patients and indicated a 7.8 times higher mortality than HGS >19.5 kg. The cut-off of HGS to stratify severity of MN and guide goal directed nutrition intervention was lower in our patient population than recommended by normative standards and likely represents the standard for the Indian population with ESLD.